Review of Cases of Occult Radiation Exposure and an Analysis of Time to Diagnosis. Issue 2 (August 2018) - Kunkler, Jillian; Adams, Tim G.; Manger, Morgan; Casagrande, Rocco
Abstract : Abstract: Radiation sickness is challenging to diagnose, and the diagnosis is often based on nonclinical data. In accidents where patients are not aware of their exposure to radiation (so-called "occult exposures"), a correct diagnosis can take weeks or months. The purpose of this study is to review the time to diagnosis of radiation sickness for occult exposures where neither the physician nor the patients are aware of their exposure. We reviewed eight case reports involving occult exposures and examined the factors that contributed to a diagnosis. We found that an average of 23 d after exposure were required for diagnosis, regardless of route of intake. In only one case was radiation injury diagnosed within the first week. Although all but one of these cases occurred in the developing world, the factors confounding diagnosis are common to the U.S. medical system. Therefore, an urgent need exists for properly training physicians on radiation sickness so they can more quickly diagnose and treat radiation exposures when the patients are unaware of the exposure event.